1999
DOI: 10.1002/(sici)1099-1263(199905/06)19:3<193::aid-jat553>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism-dependent hepatotoxicity of methimazole in mice depleted of glutathione

Abstract: Methimazole (MMI) (>0.1 mmol kg−1, p.o.) given in combination withDL‐buthionine sulphoximine (BSO) (3 mmol kg−1, i.p., 1 h before MMI administration), an inhibitor of glutathione (GSH) synthesis, caused liver injury in mice. The injury was characterized by centrilobular necrosis of hepatocytes and an increase in serum alanine transaminase (ALT) activity. Methionazole (2 mmol kg−1) alone resulted in only a marginal increase in serum ALT activity, but produced no histopathological changes in the liver. Pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 24 publications
1
30
1
Order By: Relevance
“…A CYP-dependent metabolic activation of methimazole in the liver has previously been reported by Lee and Neal (20). Methimazole is also a known substrate for flavinecontaining monooxygenases (FMO) (25) and a recent study suggests that both CYP and FMO are involved in the hepatic metabolism of methimazole (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A CYP-dependent metabolic activation of methimazole in the liver has previously been reported by Lee and Neal (20). Methimazole is also a known substrate for flavinecontaining monooxygenases (FMO) (25) and a recent study suggests that both CYP and FMO are involved in the hepatic metabolism of methimazole (23).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that in vivo GSH-depletion can potentiate the olfactory toxicity of some compounds (2,7). In GSH-depleted mice, methimazole exposure will induce a centrilobular hepatic necrosis (23,24). The effects of methimazole on the morphology of the olfactory mucosa in GSH-depleted animals or the effect of methimazole on the level of GSH in the olfactory mucosa have not been reported, however.…”
Section: Introductionmentioning
confidence: 99%
“…Styrene treatment caused a significant decrease in GSH to 70.6%, and a significant increase in lipid peroxide to 163.7% of the controls (Fig. 4), consistent with previous findings that styrene inducing oxidative stress occurs in its biotransformation process concomitant with the decrease in GSH levels (14,24). As shown in Fig.…”
Section: Inhibition By Gd Against Oxidative Stressmentioning
confidence: 98%
“…It is considered that the main sources of hepatic ROS generation are P450 enzymes, mitochondria and Kupffer cells, and that the elevated cellular oxygen radicals consequently affect hepatic GSH and lipid peroxide (2,4,14,26). Our results suggested that post-treatment with Gd could contribute to an improvement in the redox status altered by styrene treatment, and eventually would contribute to protection of rat liver from styrene damage through alleviating styrene-inducible P450 expressions such as CYP1A2, CYP2B1/2, and CYP3A2 ( Figs.…”
Section: Inhibition By Gd Against Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation